Analisis K3 pada Mesin Blow Moulding PT. XY dengan Metode HAZOP sebagai Upaya Meminimalisir Kecelakaan Kerja - Adel Milatama Putri; Nugraha, Asep Erik (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
XY is an industrial company that makes home care and food-grade plastic packaging. The purpose of this study is to analyze the risk of accidents and occupational diseases that occur and control the risk of work accidents ergonomically. In analyzing the risk of accidents and occupational diseases, an appropriate method is needed. The HAZOP (Hazard And Operability Study) method is a systematic and structured method that can analyze hazards in the operating system or processes that may pose a risk of occupational hazards. The results of the analysis indicate several sources that can result in the risk of occupational hazards including crushed feet, slipping, slashing, injuries to the musculoskeletal part, sprained feet, and hand lift pinches. Risk control can be done by conducting training based on work instructions and regulations regarding K3 to workers, cleaning the ventilation of the work area, changing work tools that are not ergonomic, conducting regular monitoring by related management, making checksheets of PPE completeness before workers enter the work area, and conducting Safety Talk once a month by the relevant management            Keywords: Ergonomic, HAZOP, Hazard, K3, and Risk